Mahinhin a tale of the Philippines - Santa Elena, Antonio E. (El Cerrito, California Downey Place Publishing House, Inc., 1984)
"A twelve-year-old girl "comes of age" in a small Philippine town near Manila during the 1950s"--Title page verso.
"A Gossypium book."
Fi-16635g donated by Prof. Mamoru Tsuda, MA UP 1977.
Keywords: Philippine literature -- Fiction; Philippines -- Fiction